The future isn t what it used to be. Changing trends and their implications for transport planning. - Litman, Todd (My University, 2012)
This report investigates how demographic and economic trends will affect future transport demands (the amount and type of travel people would choose), and their implications. Motor vehicle travel grew steadily during the Twentieth Century but has started to peak in most developed countries. Aging population, rising fuel prices, increasing urbanization, improving travel options, increasing health and environmental concerns, and changing consumer preferences are reducing demand for automobile travel and increasing demand for alternatives. Automobile travel will not disappear but at the margin (compared with current travel patterns) many people would prefer to drive less and rely more on walking, cycling, public transport and telework, provided they are convenient, comfortable and affordable. This paper discusses ways that transport policies and planning practices can respond to these changing demands.
Keywords: Individualverkehr; Fahrradverkehr; Verkehrsplanung; Verkehrspolitik; Stadtverkehr; Mobilität; Verkehrsmittelwahl; Mobilitätsverhalten; Mobilitätstrend; Trend; Fahrradnutzung; Motorisierter Verkehr; Nichtmotorisierter Verkehr; Autobesitz